Weaving cultural and generational threads in rural Philippines: the livelihood, identity, and roles of elderly women artisans in Lalaguna - Cacho, Reynald; Bua-ay, Brenda; Cortez, Leah Amor; Osena, Cyren; Samson, Maria Gracia; Dungca, Len Rose; Dejapa, Ryan (Department of Government Studies, Universitas Muhammadiyah Makassar, 2025)
Traditional weaving is a vital form of indigenous knowledge in Filipino culture. This study explores the livelihood, identity, and roles of elderly women artisans in Barangay Lalaguna, a small rural community in the Philippines. This also aims to inform heritage conservation, inclusive engagement, and culturally grounded community policies. Using a qualitative research design and inductive thematic analysis, the study examined the lived experiences of 16 elderly women weavers. Data were gathered through semi-structured interviews, with ethical protocols observed to ensure voluntary participation, confidentiality, and informed consent. Findings show that weaving serves both as a livelihood and as a cultural identity marker, deeply integrated into family life and rural community traditions. Although many women have passed on their skills to children or grandchildren, generational disinterest, migration, and modernization threaten the continuity of the craft. Despite these challenges, elderly women persist as cultural custodians and household economic contributors. The study supports the need for intergenerational learning programs, sustainable market access, and health support tailored for aging artisans. Beyond cultural significance, the findings underscore the importance of integrating weaving into cultural governance, heritage policy, and community development strategies to sustain the craft amid economic and generational change.